A reconfigurable wheelchair for mobility and rehabilitation: Design and development. Issue 1 (31st December 2016) - Goher, Khaled M.
Abstract: This paper presents the design and development of a prototype of a reconfigurable wheelchair for rehabilitation and self-assistance to fit the size of a seven years old child (average 35 kg weight). Though the developed prototype is developed at this stage to fit a child, it can be resized, after considering variations in weight and size, to fit an older adult. The developed prototype has a mechanism that enables the user to transform from sit-to-stand (STS) posture and vice versa. With the help of the developed wheelchair, the user will also be able to adjust the posture of his upper body using an adjustable back support using two linear actuators. This configuration will allow the user to use the wheelchair as a mobility device as well as for rehabilitation purposes without the need of external support. The availability of STS and back adjustment mechanisms will allow the user to do regular exercising which will enhance blood circulation as sitting for long periods inflates lower limbs disability. The proposed configuration will help in enhancing the functional capabilities of end-users allowing for increased independence and ultimately quality of life.